Variability of TSNA in U.S. Tobacco and Moist Smokeless Tobacco Products. (2020) - Oldham, M.J.; Lion, K.E.; Phillips, D.J.; Morton, M.J.; Lusso, M.F.; Harris, E.A.; Jordan, J.L.; Franke, J.E.; Strickland, J.A.
Graphical abstract: Highlights: Incoming tobaccos have extremely variable nitrosamine content. Blending reduces the variation in tobacco products, but it is still considerable. Few, if any, U.S. moist smokeless tobacco products meet the proposed FDA standard. Products must be targeted well below the proposed standard to consistently meet it. Abstract: Tobacco-specific nitrosamines (TSNAs) have been of concern to the public health community for decades and their reduction through agricultural practices, plant breeding, and tobacco processing has also been a decades-long industry effort. Despite those efforts, TSNAs, though lower, continue to be constituents of concern in tobacco products. This paper examines the TSNA levels of dark air-cured, dark fire-cured, and burley tobaccos purchased in the United States by U.S. Smokeless Tobacco Company LLC (USSTC) and of nine finished USSTC moist smokeless tobacco products. TSNA values of the incoming purchased tobaccos and the finished products showed considerable variability. For the incoming tobaccos, the coefficient of variation was generally more than 100 % for each tobacco type and for each of the measured TSNAs. The relative TSNA variability of the finished tobacco products was also considerable, averaging approximately 25 %. It was also found that the measured values for the finished products averaged well above the proposed FDA NNN proposed product standard of 1.0 μg/g dry weight. Because of the large variability in NNN values, products would have to average well below FDA's proposed product standard to be consistently compliant.